2017
DOI: 10.1080/00221686.2017.1289259
|View full text |Cite
|
Sign up to set email alerts
|

Tsunamis generated by fast granular landslides: 3D experiments and empirical predictors

Abstract: Landslides falling into water bodies can generate impulsive waves, which are considered as tsunamis. The propagating wave may be highly destructive for hydraulic structures, civil infrastructure and people living along the shorelines. A facility to study this phenomenon was set up in the laboratory of the Technical University of Catalonia. The setup consists of a new device releasing granular material at high velocity into a wave basin. A system employing laser sheets, high-speed and high-definition cameras wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 37 publications
4
41
0
Order By: Relevance
“…The wave characteristics are dependent on the landslide impact parameters [Fritz et al, 2003a[Fritz et al, , 2003b[Fritz et al, , 2004Zweifel et al, 2006;Heller and Hager, 2010;Mohammed and Fritz, 2012;McFall and Fritz, 2016;Bregoli et al, 2017;Miller et al, 2017]. The governing tsunami generation parameters investigated in this study are the water depth h, slide impact velocity v s , slide thickness s, slide width b, slide volume V s , slide length scale L s 5 V s /(sb), and shoreline radius r c .…”
Section: Physical Modelmentioning
confidence: 99%
“…The wave characteristics are dependent on the landslide impact parameters [Fritz et al, 2003a[Fritz et al, , 2003b[Fritz et al, , 2004Zweifel et al, 2006;Heller and Hager, 2010;Mohammed and Fritz, 2012;McFall and Fritz, 2016;Bregoli et al, 2017;Miller et al, 2017]. The governing tsunami generation parameters investigated in this study are the water depth h, slide impact velocity v s , slide thickness s, slide width b, slide volume V s , slide length scale L s 5 V s /(sb), and shoreline radius r c .…”
Section: Physical Modelmentioning
confidence: 99%
“…In addition, all studies were based on wave gauge data from a limited number of measurement locations. Bregoli et al (2017) demonstrated the advantages of a videometric measurement approach: First, this approach allows for a continuous representation of the water surface and therefore an adaptive tracking of specific wave conditions in the impact region. Second, in contrast to capacitance wave gauges, the measurement devices may not be damaged by the impacting slide mass.…”
Section: Introductionmentioning
confidence: 99%
“…The systematic error propagates through the empirical formulas defined after the experimental analyses. In Bregoli et al (2017), a sensitivity analysis on the proposed formulas has been performed including artificially the worst maximum systematic errors along z. A system able to measure the main parameters of experiments of tsunamis generated by landslides have been presented.…”
Section: Errors and Uncertaintymentioning
confidence: 99%
“…Particularly, the methodology allowed measuring the wave displacement at high resolution in space and high frequency in time, avoiding the classical point measurements given by probes and depicting wave series measurement which is not space dependent. For the specific experiments of tsunamis generated by landslides, the space-independent measurement is particularly beneficial because the point of maximum wave amplitude condition, corresponding with the beginning of wave propagation, forms at a certain distance from impact and it is strongly dependent on the landslide characteristics, thus varying for each run initial conditions (Bregoli et al 2017). This measurement technique addresses the observation of multiphase mass-flow complex phenomena at high details and versatility.…”
Section: Errors and Uncertaintymentioning
confidence: 99%
See 1 more Smart Citation